2021
DOI: 10.1002/cpt.2291
|View full text |Cite
|
Sign up to set email alerts
|

Exposure‐Response Relationships in Patients With HER2‐Positive Metastatic Breast Cancer and Other Solid Tumors Treated With Trastuzumab Deruxtecan

Abstract: Trastuzumab deruxtecan (T-DXd) is a HER2-targeting antibody-drug conjugate composed of a novel enzyme-cleavable linker and membrane-permeable topoisomerase I inhibitor payload. T-DXd has been approved for HER2-positive metastatic breast cancer and for HER2-positive metastatic gastric cancer. The approval in breast cancer was based on results from the DESTINY-Breast01 (U201; NCT03248492) and J101 (NCT02564900) trials. Here, we present dose justification for the approved 5.4 mg/kg every-3-weeks (Q3W) dose based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…These analyses should be interpreted with caution because they were performed in heavily pretreated and heterogeneous patients with different tumor types who received different doses and treatment durations [66,69]. These results support the established benefit-risk profile of T-DXd and do not warrant exclusion from using T-DXd or amended T-DXd dosing for any of these factors [66,69]. Further research is needed to validate these findings.…”
Section: Characterizing Patients Who Have Developed Ild/pneumonitismentioning
confidence: 70%
See 3 more Smart Citations
“…These analyses should be interpreted with caution because they were performed in heavily pretreated and heterogeneous patients with different tumor types who received different doses and treatment durations [66,69]. These results support the established benefit-risk profile of T-DXd and do not warrant exclusion from using T-DXd or amended T-DXd dosing for any of these factors [66,69]. Further research is needed to validate these findings.…”
Section: Characterizing Patients Who Have Developed Ild/pneumonitismentioning
confidence: 70%
“…While several studies have found ILD/pneumonitis to be more common in Japan, [66,67,[69][70][71] reasons underlying this association are uncertain. Population pharmacokinetic analyses suggested that T-DXd clearance was slightly lower in Japanese patients; however, there were no clinically meaningful differences in T-DXd steady-state exposure or released DXd based on patient race/country [72].…”
Section: Characterizing Patients Who Have Developed Ild/pneumonitismentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike previous studies, both the onset and recovery times for ILD in our cohort were long. However, a pooled analysis of eight single-arm phase 1 and 2 studies examining trastuzumab deruxtecan use showed that 88% of the patients who developed ILD experienced onset within 12 months of treatment [ 13 ]. In 48% of the confirmed cases, the onset time identified by the investigators was later than that identified by the ILD adjudication committee.…”
mentioning
confidence: 99%